2002
DOI: 10.1164/ajrccm.165.4.2108033
|View full text |Cite
|
Sign up to set email alerts
|

Particulate Matter Contamination of Intravenous Antibiotics Aggravates Loss of Functional Capillary Density in Postischemic Striated Muscle

Abstract: Through the increased use of less expensive and counterfeit medicines, the contamination of parenteral fluids and drugs by particulate matter poses an increasing health hazard worldwide. However, the mechanism of action of such contamination has never been conclusively demonstrated. We have systemically injected the particles contained in three different 1-g preparations of the antibiotic cefotaxime into hamsters and visualized the functional capillary density in striated skin muscle, using intravital fluoresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 40 publications
(40 reference statements)
0
73
1
3
Order By: Relevance
“…Además, en la literatura científica no se registra ningún antibiótico genérico de los empleados en nuestro país que haya sido probado por medio de ensayos clínicos controlados para establecer su eficacia clínica y seguridad, y, sin embargo, se ha asumido que son las mismas del producto innovador. La eficacia clínica no solo depende del principio activo sino de la tecnología farmacéutica (definida como los procesos de manufactura del antibiótico), la cual puede ser responsable de reducir o eliminar propiedades del fármaco, alterando su mecanismo de acción (39).…”
Section: Discussionunclassified
“…Además, en la literatura científica no se registra ningún antibiótico genérico de los empleados en nuestro país que haya sido probado por medio de ensayos clínicos controlados para establecer su eficacia clínica y seguridad, y, sin embargo, se ha asumido que son las mismas del producto innovador. La eficacia clínica no solo depende del principio activo sino de la tecnología farmacéutica (definida como los procesos de manufactura del antibiótico), la cual puede ser responsable de reducir o eliminar propiedades del fármaco, alterando su mecanismo de acción (39).…”
Section: Discussionunclassified
“…In hospital, IV fluids are not usually administered to healthy patients, but rather to ill patients (polytrauma, major surgery, microvascular blood affections, etc.). Lehr et al [105] investigated whether particulate contamination could affect the microvascular bed, using different IV solutions of cefotaxime. Functional capillary density (FCD) was analysed in non-ischemic and ischemic-reperfused muscle tissues; it was found that loss of FCD induced by particles was particularly significant in the post-ischemic tissue.…”
Section: Systemic Clinical Effectsmentioning
confidence: 99%
“…Whilst no view will be expressed on risks associated with oral medication with generics, we will focus exclusively on the intravenous administration route in severely ill patients [21]. Former work from our laboratory involved a detailed study of generics of the antibiotic cefotaxime, in which the innovator product, Claforan ® , was compared with some of its generics [21].…”
Section: Introductionmentioning
confidence: 99%
“…Whilst no view will be expressed on risks associated with oral medication with generics, we will focus exclusively on the intravenous administration route in severely ill patients [21]. Former work from our laboratory involved a detailed study of generics of the antibiotic cefotaxime, in which the innovator product, Claforan ® , was compared with some of its generics [21]. This in vivo study was designed to test the possible functional significance of particulate contaminants, and aimed at simulating the state of the microcirculation in a typical patient in the intensive care unit (ICU), that is, generally with some degree of multiple organ dysfunction syndrome (MODS), in the form of microcirculatory dysfunction [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation